Study on the ecological water demand security assessment for the Panjin wetland based on landscape pattern. Issue 4 (31st March 2023) - Cheng, Qian; Chen, Fujiang; Wang, Tieliang
Abstract: The model was used to predict and analyze the future changes in the total ecological water demand of the Panjin wetland, with a view to providing some scientific reference for the optimal allocation of regional water resources and the sustainable development of wetlands. The results showed that (1) the quality of the habitat environment in the Panjin wetland has a great influence on the change of the total water demand, and the total ecological water demand in the Panjin wetland will continue to decrease in the future. (2) There is a clear correlation between landscape pattern and ecological water demand. (3) The distribution characteristics of the landscape pattern are greatly influenced by political factors, thus affecting the total ecological water demand of the Panjin wetland. HIGHLIGHTS: The landscape pattern changes in the Panjin wetland from 1989 to 2017 were investigated. The ecological water demand of the Panjin wetland was calculated. The important factor affecting the ecological water demand security of the Panjin wetland was habitat quality. The ecological water demand of the Panjin wetland was predicted and assessed to provide a basis for scientific wetland management. Graphical Abstract